Copper oxide porous nanoflower catalyst as well as preparation method and application thereof

The template method was used to prepare porous copper oxide nanoflower catalysts, which solved the problem of low active site density in the electroreduction reaction of carbon monoxide by copper-based catalysts. This method achieved high efficiency, high selectivity and high yield of carbon monoxide electroreduction to multi-carbon products, and is suitable for industrial applications.

CN121023558APending Publication Date: 2025-11-28YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511086965.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing copper-based catalysts in the electroreduction reaction of carbon monoxide suffer from low density of surface active sites and lack of precise control over the adsorption and desorption capacity of key intermediates, resulting in uncontrollable product distribution and low current density, making it difficult to efficiently prepare highly selective multi-carbon products.

Method used

Porous copper oxide nanoflower catalysts were prepared using a template method. The nanoflowers were formed by hydrothermal synthesis and removal of the template agent, resulting in a porous flower-like structure with a size of 1.8–2.2 μm and a pore size of 100–150 nm. This improved the active site density and carbon monoxide electroreduction efficiency of the catalyst.

Benefits of technology

The method achieves high selectivity and high yield of carbon monoxide electroreduction to multi-carbon products. The Faraday efficiency of multi-carbon products in the flow electrolyzer exceeds 90%, and the Faraday efficiency of ethylene exceeds 40%. It is suitable for industrial application of carbon monoxide electroreduction to prepare multi-carbon products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121023558A_ABST
    Figure CN121023558A_ABST
Patent Text Reader

Abstract

The invention provides a copper oxide porous nanoflower catalyst and a preparation method and application thereof.The catalyst is in a porous flower shape, the size of nanoflowers ranges from 1.8 micrometers to 2.2 micrometers, the thickness of nanoflowers ranges from 50 nanometers to 150 nanometers, and the pore diameter of nanoflowers ranges from 100 nanometers to 150 nanometers. The preparation method comprises the steps that copper salt, ammonia water and polystyrene spheres are fully mixed and then subjected to a complete hydrothermal reaction at the temperature of 70 DEG C to 120 DEG C, and the copper oxide porous nanoflower catalyst is obtained. And after cooling, centrifuging, washing and drying, washing away the residual polystyrene template by using a solvent, and centrifuging and thoroughly drying to obtain the copper oxide porous nanoflower catalyst. The obtained copper oxide porous nanoflower catalyst can be used for a carbon monoxide electroreduction reaction, the prepared catalyst has high carbon monoxide electroreduction electroreaction catalytic activity by introducing a nanometer hole structure on the nanometer size, and the high yield of carbon monoxide to multi-carbon products and the single selectivity of ethylene products are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical catalytic materials, specifically relating to a copper oxide porous nanoflower catalyst and its preparation method, as well as its application in the electrochemical reduction of carbon monoxide to prepare multi-carbon products. Background Technology

[0002] With the urgent global need for carbon neutrality, the conversion of carbon dioxide (CO2) into high-value-added chemicals using electrochemical technology has become an important direction for carbon resource utilization. However, the direct electrochemical reduction of CO2 to produce multi-carbon (C2) compounds remains a challenge. 2+ The products (such as ethylene, ethanol, and acetic acid) face bottlenecks such as low selectivity, high overpotential, and poor stability. In recent years, two-step processes (CO2→CO→C) have emerged as a solution. 2+ This research is gradually becoming a hot topic, involving the generation of CO through efficient CO2 reduction or commercial processes (such as solid oxide electrolyzers), followed by the electroreduction of carbon monoxide (COR) to convert it into high-value C2₊ products. COR exhibits significant advantages in alkaline electrolytes: it can avoid the carbonate side reaction of direct CO2 electroreduction and increase the C2₊ content. 2+ Selectivity and system stability.

[0003] Current research indicates that copper-based catalysts remain the only efficient catalysts capable of catalyzing the conversion of CO2 and CO into C. 2+ However, conventional copper-based catalysts (such as copper foil and nanoparticles) have a wide variety of active sites with low density, lacking precise control and efficient conversion of the adsorption and desorption capacity of key intermediates (such as CO and C=C=O). In the COR process, they still suffer from uncontrollable product distribution and low current density, making it difficult to achieve efficient single COR at high current densities. 2+ The synthesis of the product. Therefore, the search for copper-based catalysts with high surface active site density and their structural optimization are crucial for the high-efficiency and high-selectivity electrochemical reduction of CO to C. 2+ Products are of paramount importance, which in turn drives the industrialization of producing high-value-added carbon-containing products from CO2. Summary of the Invention

[0004] This invention provides a method for preparing porous copper oxide nanoflower catalysts, which improves the efficiency of copper oxide catalysts in the electroreduction reaction of carbon monoxide to produce multi-carbon products. Specifically, a copper oxide material with a template agent is first hydrothermally synthesized using a template method, and then the template agent is washed away to obtain the porous copper oxide nanoflower catalyst. This catalyst achieves high selectivity and high yield in the reduction of carbon monoxide to multi-carbon products. The method is simple, reproducible, and has the potential for large-scale production and application.

[0005] The technical solution adopted in this invention is as follows: This invention provides a copper oxide porous nanoflower catalyst, wherein the copper oxide porous nanoflower catalyst is porous flower-shaped, the nanoflower size is 1.8~2.2 micrometers, the thickness is 50~150 nanometers, and the pore size is 100~150 nanometers.

[0006] This invention provides a method for preparing a porous copper oxide nanoflower catalyst, comprising the following steps: Step 1: Mix the copper salt, ammonia, and polystyrene microspheres (240 nm in diameter) solution, and then stir magnetically at room temperature until the mixture is homogeneous; Step 2: Transfer the mixed solution to the inner lining of a polytetrafluoroethylene hydrothermal reactor, seal it to a stainless steel hydrothermal reactor, and allow it to react fully hydrothermally for 10-12 hours to obtain a mixture of copper oxide porous nanoflowers and other reaction products. Step 3: After the mixture is allowed to stand and cool, the liquid is discarded, solvent is added, centrifuged, washed, and dried to obtain copper oxide porous nanoflowers mixed with template agent; Step 4: Add N,N-dimethylformamide to the copper oxide porous nanoflowers mixed with template agent, sonicate the resulting mixed solution thoroughly to wash away the template agent, then centrifuge, wash, and dry to obtain copper oxide porous nanoflowers; Step 5: Add solvent and perfluorosulfonic acid polymer solution to copper oxide porous nanoflower catalyst, sonicate the resulting mixed solution, and uniformly load the solution onto carbon material using a spray gun. After drying, a carbon material-based copper oxide porous nanoflower catalyst gas diffusion electrode is obtained.

[0007] As a preferred embodiment, the copper salt includes, but is not limited to, one or more of copper chloride, copper nitrate, copper sulfate, and copper acetate.

[0008] As a preferred method, the molar ratio of copper salt to ammonia is 1:(10~12), the concentration of polystyrene microsphere solution is 50~200 mg / mL, the magnetic stirring speed is 800~1200 rpm, and the stirring time is 30~60 minutes.

[0009] As a preferred method, the temperature of the hydrothermal reaction in step 2 is 70~120 degrees Celsius.

[0010] As a preferred method, the solvent added in step 3 is one or more of deionized water, ethanol, and isopropanol.

[0011] As a preferred method, in step 3, the number of centrifugations is 2 to 5, the centrifugation speed is 9000 to 13000 rpm, and the centrifugation time is 6 to 10 minutes.

[0012] As a preferred method, in step 4, the number of centrifugations is 3 to 5, the centrifugation speed is 9000 to 13000 rpm, and the centrifugation time is 6 to 10 minutes.

[0013] As a preferred method, the carbon material in step 5 is 30T carbon paper.

[0014] As a preferred method, the ultrasound time in step 5 is 30-60 minutes and the temperature is room temperature.

[0015] As a preferred method, the temperature during the preparation of the gas diffusion electrode in step 5 is 60-80 degrees Celsius; the drying conditions are drying at 60-80 degrees Celsius for 30-60 minutes.

[0016] The present invention also provides the application of the copper oxide porous nanoflower catalyst described in any of the above technical solutions or the copper oxide porous nanoflower catalyst obtained by any of the preparation methods described in the above technical solutions in the carbon monoxide electroreduction reaction.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: The copper oxide porous nanoflower catalyst provided by this invention has a specific structure and morphology. By introducing a nanopore structure at the nanoscale, the prepared catalyst has high catalytic activity for the electroreduction of carbon monoxide, achieving high yield of carbon monoxide to multi-carbon products and single selectivity for ethylene products.

[0018] This invention prepares copper oxide porous nanoflower catalysts via a template method. The preparation steps are simple, reproducible, and have the potential for large-scale production and application.

[0019] The copper oxide porous nanoflower catalyst provided by this invention can achieve a multi-carbon product Faradaic efficiency of over 90% in a flow electrolytic cell, with a Faradaic efficiency of over 40% for ethylene, making it suitable for industrial applications in the preparation of multi-carbon products by carbon monoxide electroreduction. Attached Figure Description

[0020] Figure 1 This is a scanning electron microscope image of the polystyrene microspheres used as templates in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the copper oxide porous nanoflower catalyst obtained in Example 1 of the present invention; Figure 3 The X-ray diffraction patterns of the porous copper oxide nanoflower catalyst, commercial copper oxide nanoparticles, and standard copper oxide crystals obtained in Example 1 of this invention are shown below. Figure 4 The double-layer charge-discharge curves (a, c) of the copper oxide porous nanoflower catalyst and commercial copper oxide nanoparticles obtained in Example 2 of the present invention and their corresponding double-layer capacitance values ​​(b, d) are shown in an H-type electrolytic cell. Figure 5The Faraday efficiency of each product of the carbon monoxide electroreduction reaction in a three-electrode flow electrolytic cell for the copper oxide porous nanoflower catalyst (a) and commercial copper oxide nanoparticles (b) obtained in Example 3 of this invention is shown at different current densities.

[0021] Figure 6 The partial current density-reaction potential curves of ethylene with double-layer capacitance normalized using the copper oxide porous nanoflower catalyst (a) and commercial copper oxide nanoparticles (b) obtained in Example 3 of the present invention are shown. Detailed Implementation

[0022] Preferred embodiments of the present invention have been described in conjunction with examples; however, it should be understood that these descriptions are merely for further illustrating the features and advantages of the invention and are not intended to limit the scope of the claims.

[0023] All raw materials used in this invention are not particularly limited in their source; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.

[0024] The purity of all raw materials used in this invention is not particularly limited, but analytical grade or the purity requirements conventional in the field of atomic layer deposition are preferred.

[0025] All raw materials and processes of this invention are designated by or abbreviated as conventional designations or abbreviations in the field. Each designation or abbreviation is clearly defined in its relevant application area. Those skilled in the art can purchase them from commercially available sources or prepare them by conventional methods, or implement them using appropriate equipment, based on the designation, abbreviation, and corresponding application.

[0026] The present invention will be further described in detail below with reference to embodiments: Example

[0027] This embodiment prepared a porous copper oxide nanoflower catalyst, specifically including the following steps: Step 1: Take 68.2 mg of copper chloride dihydrate, dissolve it in 25 mL of deionized water in a 40 mL clean glass bottle, sonicate until completely dissolved, then add 0.6 mL of ammonia water (28% by mass) to the resulting solution, mix well, then add a polystyrene microsphere (240 nm in diameter) solution (100 mg / mL) to the resulting dark blue solution, and stir magnetically for 60 minutes at room temperature until fully mixed; Step 2: Transfer the mixed solution to the inner lining of a polytetrafluoroethylene hydrothermal reactor, seal it to a stainless steel hydrothermal reactor, and hydrothermally react at 100 degrees Celsius for 12 hours to obtain a mixture of copper oxide porous nanoflowers and other reaction products. Step 3: After the mixture cools naturally, discard the liquid, add 80 ml of deionized water to the remaining solid, centrifuge at a preferred speed of 12000 rpm for 5 minutes, discard the liquid, repeat this step twice, and then vacuum dry the obtained solid at 60 degrees Celsius for 6 hours to obtain copper oxide porous nanoflowers mixed with template agent. Step 4: Add 20 mL of N,N-dimethylformamide to the copper oxide porous nanoflowers mixed with the template agent, sonicate for 60 minutes to fully disperse, then centrifuge at a preferred speed of 12,000 rpm, discard the supernatant, repeat this step twice, then add 20 mL of ethanol to the obtained solid, centrifuge at a preferred speed of 12,000 rpm, discard the supernatant, and then vacuum dry at 60 degrees Celsius for 6 hours to obtain the copper oxide porous nanoflower catalyst.

[0028] The copper oxide porous nanoflower catalyst obtained in this embodiment was characterized.

[0029] Figure 1 Scanning electron microscope (SEM) images of polystyrene microspheres (240 nm in diameter) used as template agents. The images show that the polystyrene microspheres have a uniform morphology and a diameter of approximately 240 nm. Figure 2 The image shows a scanning electron microscope (SEM) image of the obtained porous copper oxide nanoflower catalyst. The image reveals that the porous copper oxide nanoflower catalyst exhibits a porous flower-like structure, with nanoflower sizes ranging from 1.8 to 2.2 micrometers, thicknesses from 50 to 150 nanometers, and pore sizes from 100 to 150 nanometers. Figure 3 The X-ray diffraction patterns are shown for the obtained porous copper oxide nanoflower catalyst, commercial copper oxide nanoparticles, and standard copper oxide crystals. The diffraction patterns reveal that both the synthesized porous copper oxide nanoflower catalyst and the commercial copper oxide nanoparticles are copper oxide phases. Example

[0030] The copper oxide porous nanoflower catalyst prepared in Example 1 was subjected to double-layer capacitance charge-discharge tests using a three-electrode H-type electrolytic cell.

[0031] The specific steps are as follows: Step 1: Take 10 mg of copper oxide porous nanoflower catalyst, add 2 mL of ethanol and 20 μL of perfluorosulfonic acid polymer solution, sonicate the resulting mixed solution for 60 minutes, and drop 226 μL of the dispersed mixed solution onto a glassy carbon electrode under an infrared lamp. After the ethanol evaporates, copper oxide porous nanoflower catalyst loaded on a glassy carbon electrode is obtained. Step 2: In a three-electrode H-type electrolytic cell, the copper oxide porous nanoflower catalyst supported on a glassy carbon electrode was used as the working electrode, a graphite rod electrode as the counter electrode, and a saturated calomel electrode as the reference electrode. Argon-saturated potassium chlorate at 0.1 mol / L was used as the electrolyte. During testing, a constant current method was first used, applying a current density of -1 mA / cm² to the working electrode for 20 minutes. Then, cyclic voltammetry was performed, with the high potential at -0.6 V relative to the reference electrode and the low potential at -0.67 V relative to the reference electrode. The scan rate was set to 10–60 mV / s, with intervals of 10 mV / s, and 10 scan cycles at the same scan rate. This yielded the charge-discharge curves of the double-layer capacitance of the copper oxide porous nanoflower catalyst at different scan rates. Step 3: Plot the absolute values ​​of the maximum values ​​of the cathode and anodic charge-discharge currents of the double-layer capacitance charge-discharge curves of the copper oxide porous nanoflower catalyst at different scan rates against the scan rate, and perform linear fitting on the obtained data using the least squares method. The slope of the obtained fitted line is the double-layer capacitance value of the copper oxide porous nanoflower catalyst.

[0032] The double-layer capacitance of commercial copper oxide nanoparticles was obtained using the same procedure.

[0033] Figure 4 The figures show the charge-discharge curves (a, c) of the porous copper oxide nanoflower catalyst obtained in Example 1 and commercial copper oxide nanoparticles in an H-type electrolytic cell, along with their corresponding double-layer capacitance values ​​(b, d). A comparison of the double-layer capacitance values ​​reveals that, under the same loading, the porous copper oxide nanoflower catalyst exhibits a lower double-layer capacitance, indicating a smaller electrochemically active area. Example

[0034] The copper oxide porous nanoflower catalyst prepared in Example 1 was subjected to double-layer capacitance charge-discharge tests using a three-electrode flow electrolysis cell.

[0035] The specific steps are as follows: Step 1: Take 20 mg of copper oxide porous nanoflower catalyst, add 10 mL of isopropanol and 40 μL of perfluorosulfonic acid polymer solution, sonicate the resulting mixture for 60 minutes, and spray the resulting mixture evenly onto a 4 cm² 30T carbon paper gas diffusion electrode using an air spray gun at a constant temperature of 80 degrees Celsius. Continue to maintain the temperature for 30 minutes to allow the isopropanol to evaporate, thus obtaining copper oxide porous nanoflower catalyst supported on the gas diffusion electrode. Step 2: In a three-electrode flow electrolytic cell, a porous copper oxide nanoflower catalyst supported on a gas diffusion electrode was used as the working electrode, an iridium oxide supported on a titanium mesh as the counter electrode, a mercury oxide electrode as the reference electrode, and 1 mol / L potassium hydroxide as the electrolyte. During testing, a constant current method was used, applying a current density of -100 to -500 mA / cm² to the working electrode for 20 minutes at each current density. The gaseous products were detected by gas chromatography, and the liquid products were detected by liquid nuclear magnetic resonance spectroscopy. The product concentration was calculated, and the Faraday efficiency was calculated based on the gas and liquid flow rates and the current applied by the electrochemical workstation. After the potential stabilized, the resistance relative to the reference electrode was measured at the working potential, and the resistance was corrected with a 100% correction factor.

[0036] Figure 5 The faradaic efficiency and ethylene yield of the copper oxide porous nanoflower catalyst (a) and commercial copper oxide nanoparticles (b) in the carbon monoxide electroreduction reaction in a three-electrode flow electrolyzer at different current densities are shown. By comparing the product distribution in the carbon monoxide electroreduction reaction, it can be seen that the copper oxide porous nanoflower catalyst exhibits higher selectivity for multi-carbon products and lower hydrogen evolution side reactions, and achieves an ethylene faradaic efficiency exceeding 40%, which is more than 10% higher than that of commercial copper oxide.

[0037] Figure 6 The figures show the partial current density-reaction potential curves of ethylene in the carbon monoxide electroreduction reaction of the copper oxide porous nanoflower catalyst (a) obtained in Example 1 and commercial copper oxide nanoparticles (b) in a three-electrode flow electrolyzer, normalized to the double-layer capacitance value. This index represents the intrinsic activity of the catalyst for the electroreduction of carbon monoxide to ethylene. As shown in the figure, at the same potential, the copper oxide porous nanoflower catalyst exhibits a higher partial current density for the ethylene product, indicating that it has higher intrinsic activity for the electroreduction of carbon monoxide to ethylene than the commercial copper oxide nanoparticles. This demonstrates that by introducing a nanoporous structure at the nanoscale, the selectivity of copper oxide for the electroreduction of carbon monoxide to ethylene can be improved.

[0038] The scope of protection of this invention is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements that are not different from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims, then these other embodiments should also be included within the scope of the claims. The technical content for which protection is sought in this invention has been fully described in the claims.

Claims

1. A copper oxide porous nanoflower catalyst, characterized in that, The copper oxide porous nanoflower catalyst is porous and flower-shaped, with a nanoflower size of 1.8~2.2 micrometers, a thickness of 50~150 nanometers, and a pore size of 100~150 nanometers.

2. The method for preparing a porous copper oxide nanoflower catalyst according to claim 1, characterized in that, Includes the following steps: Step 1: Mix the copper salt, ammonia water, and polystyrene microsphere solution, and then stir magnetically at room temperature until the mixture is homogeneous; Step 2: Transfer the mixed solution to the inner lining of a polytetrafluoroethylene hydrothermal reactor, seal it to a stainless steel hydrothermal reactor, and allow it to react fully hydrothermally for 10-12 hours to obtain a mixture of copper oxide porous nanoflowers and other reaction products. Step 3: After the mixture is allowed to stand and cool, the liquid is discarded, solvent is added to the remaining solid, centrifuged, washed, and dried to obtain copper oxide porous nanoflowers mixed with template agent; Step 4: Add N,N-dimethylformamide to the copper oxide porous nanoflowers mixed with the template agent, sonicate the resulting mixed solution thoroughly, and after the template agent is dissolved, centrifuge, wash, and dry to obtain the copper oxide porous nanoflower catalyst. Step 5: Add solvent and perfluorosulfonic acid polymer solution to copper oxide porous nanoflower catalyst, sonicate the resulting mixed solution, and uniformly load the solution onto carbon material using a spray gun. After drying, a carbon material-based copper oxide porous nanoflower catalyst gas diffusion electrode is obtained.

3. The method for preparing a porous copper oxide nanoflower catalyst according to claim 2, characterized in that, The copper salt in step 1 is one or more of copper chloride, copper nitrate, copper sulfate, and copper acetate. The molar ratio of copper salt to ammonia is 1:(10~12). The diameter of the polystyrene microsphere solution is 240 nanometers, the concentration is 50~200 mg / mL, the magnetic stirring speed is 800~1200 rpm, and the stirring time is 30~60 minutes.

4. The method for preparing a porous copper oxide nanoflower catalyst according to claim 2, characterized in that, The temperature of the hydrothermal reaction in step 2 is 70~120 degrees Celsius.

5. The method for preparing a porous copper oxide nanoflower catalyst according to claim 2, characterized in that, The solvent added in step 3 is one or more of deionized water, ethanol, and isopropanol. The number of centrifugations is 2 to 5, the centrifugation speed is 9000 to 13000 rpm, and the centrifugation time is 6 to 10 minutes.

6. The method for preparing a porous copper oxide nanoflower catalyst according to claim 2, characterized in that, In step 4, the number of centrifugations is 2 to 5, the centrifugation speed is 9000 to 13000 rpm, and the centrifugation time is 6 to 10 minutes.

7. The method for preparing a porous copper oxide nanoflower catalyst according to claim 2, characterized in that, In step 5, the solvent is one or more of deionized water, ethanol, and isopropanol. The mass ratio of copper oxide porous nanoflowers to solvent is 1:(160~200), and the volume ratio of perfluorosulfonic acid polymer solution to solvent is 1:(80~100).

8. The method for preparing a porous copper oxide nanoflower catalyst according to claim 2, characterized in that, The carbon material used in step 5 is carbon paper.

9. The method for preparing a porous copper oxide nanoflower catalyst according to claim 2, characterized in that, In step 5, the ultrasonic time is 30-60 minutes and the temperature is room temperature; the temperature for preparing the gas diffusion electrode is 60-80 degrees Celsius; and the drying conditions are drying at 60-80 degrees Celsius for 30-60 minutes.

10. The application of the copper oxide porous nanoflower catalyst according to claim 1 or the copper oxide porous nanoflower catalyst obtained by the method according to any one of claims 2-9, characterized in that, The copper oxide porous nanoflower catalyst is used in the electrocatalytic reduction reaction of carbon monoxide.